MASALAH REINTEGRASI SOSIAL DAN EKONOMI MIGRAN KEMBALI* - Setiadi Setiadi (Populasi, 2001)
At the last ten years, the migration trend has become interested to be studied. The feminization trend of international migration is one of the aspects that need further analysis. Unfortunately, the existing studies have not been able to answer the issue. One of the issues is the problem of life of women return migrant on the context of the process of reintegration in the social economic life and social culture of households and origin area community. This research shows that the changes of the material basics of women return migrant effects on the changing of the social economic aspiration. On the other hand, migrating can improve the bargaining position of women on the household life. It seems that migrant can act as the changing agent in the society. The reducing of the old values occurs along with the migrant reintegration process resulting the life pattern in some aspects of the household and community life differs than before the migration.